DNA methylation signatures follow preformed chromatin compartments in cardiac myocytes. Issue 1 (December 2017) - Nothjunge, Stephan; Nührenberg, Thomas; Grüning, Björn; Doppler, Stefanie; Preissl, Sebastian; Schwaderer, Martin; Rommel, Carolin; Krane, Markus; Hein, Lutz; Gilsbach, Ralf
Abstract Storage of chromatin in restricted nuclear space requires dense packing while ensuring DNA accessibility. Thus, different layers of chromatin organization and epigenetic control mechanisms exist. Genome-wide chromatin interaction maps revealed large interaction domains (TADs) and higher order A and B compartments, reflecting active and inactive chromatin, respectively. The mutual dependencies between chromatin organization and patterns of epigenetic marks, including DNA methylation, remain poorly understood. Here, we demonstrate that establishment of A/B compartments precedes and defines DNA methylation signatures during differentiation and maturation of cardiac myocytes. Remarkably, dynamic CpG and non-CpG methylation in cardiac myocytes is confined to A compartments. Furthermore, genetic ablation or reduction of DNA methylation in embryonic stem cells or cardiac myocytes, respectively, does not alter genome-wide chromatin organization. Thus, DNA methylation appears to be established in preformed chromatin compartments and may be dispensable for the formation of higher order chromatin organization. Chromatin is organized in higher order A and B compartments, reflecting active and inactive chromatin. Here, the authors provide evidence that in cardiac myocytes DNA methylation is established in preformed chromatin compartments and may be dispensable for higher order chromatin organization.